Prevalence of Clinical Periodontitis and Putative Periodontal Pathogens among South Indian Pregnant Women - Chaitanya Tellapragada; Vandana Kalwaje Eshwara; Shashidhar Acharya; Parvati Bhat; Asha Kamath; Shashidhar Vishwanath; Chiranjay Mukhopadhyay (International Journal of Microbiology)
In view of recent understanding of the association of periodontal infections and adverse pregnancy outcomes, the present investigation was undertaken to study the periodontal infections among 390 asymptomatic pregnant women and to find an association of bacterial etiologies with the disease. Prevalence of gingivitis was 38% and clinical periodontitis was 10% among the study population. Subgingival plaque specimens were subjected to multiplex PCR targeting ten putative periodontopathogenic bacteria. Among the periodontitis group, high detection rates of Porphyromonas gingivalis (56%), Prevotella nigrescens (44%), Treponema denticola (32%), and Prevotella intermedius (24%) were noted along with significant association with the disease (P<0.05).